Dampak Negatif Pertikel Debu dan Timbal dalam Gas Buang Kendaraan Bermotor terhadap Kesehatan Masyarakat di Kabupaten Bantul - Endah Saptutyningsih (EKO-REGIONAL, 2009)
This economic valuation research proposes to determine health cost that impacted by PM10 and Tetra Etil Lead (Pb) on air pollution, estimate revenue counted from air quality changing from 25% PM10 and Pb descent in Bantul. Economic valuation of air pollution impacted by vapor from auto vehicle gasoline to people health is counted by determining 4 factors: dose response coefficient, number of people who impacted, pollutant changing which measured, and economic valuation to health. Function response exposure method is applied to detect the impact of how many people will change if pollution was changed. This research shows, by dose response function method, the most accentuate of health people impacted by PM10  pollution on 2007 is non-working cases and throat irritation cases.Keyword:  dose response function, exposure response function, PM10